EFFECT OF TEACHING MATERIALS BIKIN DONGENG YUK! LEARNING OUTCOMES OF CLASS V PRIMARY SCHOOL - Galih Dani Septiyan Rahayu; Ruli Setiyadi Setiyadi (IKIP Siliwangi, 2018)
The research entitled the influence of teaching materials bikin dongeng yuk! towards the learning outcomes of elementary school students. This research is motivated by the low student learning outcomes in Indonesian language learning, especially the material elements of the story and the lack of teaching materials about language learning in elementary schools. The use of existing language teaching materials still cannot maximize learning due to the lack of interesting teaching materials. The purpose of this study was to improve the learning outcomes of elementary students in Anggrawati I Elementary School, Maja Subdistrict, Majalengka District and Sukaraja Elementary School I, Sukaraja District, Sukabumi Regency. The use of the method in this study is pre-experimental with one group pretest-posttest design which aims to determine the effect of teaching materials to make a fairy tale !. The instrument used in this study is the observation sheet in the form of a checklist with the indicators are the intrinsic elements of the story. The results of the study were an increase in the learning outcomes of elementary school students, especially in the material elements of the story.Keywords: Teaching Materials bikin dongeng yuk!, Learning Outcomes